POTENSI KOMODITAS PANGAN DALAM MENDUKUNG KETAHANAN PANGAN DI KECAMATAN WEWARIA KABUPATEN ENDE - Nona, Reyna Virginia; Leha, Ernesta (ANALISIS, 2023)
Abstract It is necessary to know the description of the availability of food commodities in a region in order to support the realization of food security. This study aims to determine: 1) Basic food commodities in Wewaria District, 2) Growth dominant food commodities that have the potential to be developed in Wewaria District. The research used the library study method. Data analysis techniques are adapted to the research objectives, namely the Location Quotient (LQ) formula to determine basic food commodities, and Growth Ratio Model (MRP) analysis to determine potential economic activity based on growth criteria. This study shows that the basic commodity is paddy rice, and the results of the MRP analysis show that corn and shorgum are the dominant growth food commodities. This research is useful for the Government of Ende Regency in formulating policies related to food potential and efforts to meet food needs for the community both in Wewaria District and at the Ende Regency level. Keywords: security, food, commodity, base, growth